Copper(i) halide and palladium(ii) chloride complexes of 4-thioxo[1, 3, 5]oxadiazocines: synthesis, structure and antibacterial activity. (4th May 2020) - Kuzovlev, Andrey S.; Volkova, Daria A.; Parfenova, Irina V.; Kulakov, Ivan V.; Shkirdova, Alena O.; Zamilatskov, Ilya A.; Chernyshev, Vladimir V.; Rybakov, Victor B.; Tyurin, Vladimir S.; Fefilov, Nikolay N.; Vasilchenko, Alexey S.
Abstract : The first copper(i ) and palladium(ii ) complexes containing monastrol analogs, 4-thioxo[1, 3, 5]oxadiazocine derivatives, have been synthesized. The complexes demonstrated significant antibacterial activity in contrast to free heterocyclic thiones. Abstract : Copper(i ) halide and palladium(ii ) chloride complexes with tricyclic monastrol analogs containing the oxadiazocine ring have been synthesized and studied. The structures of the complexes were investigated with IR, NMR and UV spectroscopy. Two complexes, [Cu(L 1 )2 Cl] and [Pd(L 1 )2 Cl2 ], were structurally characterized by X-ray single-crystal and powder diffraction respectively. All the obtained coordination compounds were mononuclear. The ligands were coordinated with copper(i ) and palladium(ii ) only via the soft sulfur atoms of thiocarbamide fragments, while the harder nitrogen and oxygen atoms remained uncoordinated. The palladium center was coordinated by two Cl ions and two S atoms from two 4-thioxo[1, 3, 5]oxadiazocine ligands in a distorted square-planar geometry. Copper(i ) formed a trigonal planar geometry. The complexes demonstrated significant antibacterial activity towards the Escherichia coli K12 TG 1 bacterial strain in contrast to the free ligands, which didn't show any noticeable activity.